Co-Creating Nature: Tourist Photography as a Creative Performance - Katrín Anna Lund (Humanities, 2023)
This article examines tourism nature photography as a creative and sensual activity. Based on a collection of photographs gathered from tourists in the Strandir region in northwest Iceland, I demonstrate how photographing nature is a more-than-human practice in which nature has full agency. Much has been written about tourist photography since John Urry theorised about the tourist gaze in the early 1990s; this view has been criticised, especially in the light of the performance turn in tourism studies.It has, for example, been noted that tourist photography is not just about the gazing tourist, but also about social relations that the surrounding landscape partly directs and stages. It has also been argued that, as photographing tourists, we become ‘concerned with the artistic production of ourselves’. Photography is thus a practise that is relational and sensual and that cannot be reduced to the seeing eye. However, whilst emphasising the tourist as a creative being, the surrounding landscape has been left out as a stage and its active agency ignored. I address the complex, more-than-human relations that emerge in the photographs collected in Strandir. I argue that the act of photographing, as a performative practice, is improvisational and co-creative, and the material surroundings have a direct and active agency. As has been demonstrated, photography communicates ‘not through the realist paradigm but through lyrical expressiveness’ and, thus, it may be argued that tourist photography is a poetic practice of making, as it weaves together the sensing self and the vital surroundings in the moving moment that the photograph captures.